Occupational noise exposure and maternal pregnancy complications: register-based cohort from urban areas in four Nordic countries - Pasanen, Tytti P; Tiittanen, Pekka; Roswall, Nina; Persson Waye, Kerstin; Selander, Jenny; Sanchez Martinez, Nestor; Sjöström, Mattias; Vincens, Natalia; Ögren, Mikael; Aasvang, Gunn Marit; Evandt, Jorunn; Krog, Norun Hjertager; et al. (Occupational and environmental medicine (London, England), 2025)
ObjectiveTo assess the role of occupational noise exposure on pregnancy complications in urban Nordic populations.MethodsA study population covering five metropolitan areas in Denmark, Finland, Norway and Sweden was generated using national birth registries linked with occupational and residential environmental exposures and sociodemographic variables. The data covered all pregnancies during 5–11 year periods in 2004‒2016, resulting in 373 184 pregnancies. Occupational noise exposure was based on a Swedish-developed job-exposure-matrix, containing measured A-weighted annual 8 hour noise levels (LAeq8h), and linked with person-specific job-history. Outcomes included diagnosed gestational diabetes, gestational hypertension, mild pre-eclampsia and severe pre-eclampsia. The data were analysed with logistic regression models separately in each country, adjusting for maternal (age, parity, birth year, education and marital status) and residential environmental factors (low neighbourhood income, NO2 and green and blue space). The results were combined by meta-analysis.ResultsOccupational noise exceeding 80 dB, compared with less than 70 dB, was associated with an increased odds of gestational diabetes in all countries, with a combined OR of 1.26 (95% CI 1.04 to 1.51), and mild pre-eclampsia in all countries except Finland, resulting in a combined OR of 1.22 (95% CI 0.99 to 1.51). Further adjustment by maternal body-mass index attenuated these associations. No association with gestational hypertension or severe pre-eclampsia was found.ConclusionsRegister data from four nationalities show that gestational diabetes and, tentatively, mild pre-eclampsia was increased among pregnant workers working in occupations where noise levels exceed 80 dB LAeq8h but not in occupations with lower noise levels.